Simulation of heat generation in friction surface cladding (FSC) of multilayer AA2024 - Muhamad Afiq, Izuan; Nor Imrah, Yusoff (Penerbit UMP, 2022)
Friction surface cladding (FSC) is a solid-state cladding process that produces a thin metal layer on the substrate. It can be utilised at the surface to change the mechanical and corrosive properties of structural materials. There is a lack of retaining between the clad material and the substrate, resulting in loss of retaining between the clad material and the substrate. In this project, to estimate the heat generation during friction surface cladding (FSC) process for multilayer AA2024 using comsol multiphysics 5.5. The process parameter with different layer thickness has been investigated. Clad layer thickness 0.4mm -1.6mm (0.4mm each layer) with constant rotation speed 600rpm and translation speed 30mm/min was tested in this simulation to detect heat distribution. From the simulation result, the temperature increases significantly when cladding process started. With the thickness layer 0.4mm, the simulation shows the highest temperature which is same as the experimental result. For the conclusion, the clad layer thickness can affect the heat generation during friction surface cladding. As a result, the rate of heat generation is inversely proportional to the thickness of the clad layer. The thicker the clad layer, the lower the rate of heat distribution.